Spatial and Temporal Variations of Atmospheric PM10 and Air Pollutants Concentration in Upper Northern Thailand during 2006–2016 - Radshadaporn Janta (2020)
© 2020 King Mongkut’s University of Technology North Bangkok. All Rights Reserved. Hourly data of PM10 mass concentrations obtained from 13 air pollutants monitoring stations in 8 provinces of the Northern Thailand by Pollution Control Department (PCD) and hotspot data collected from NASA’s Earth Observatory website during January 2006 – December 2016 were analyzed. The annual mean, episode mean and non-episode mean of PM10 concentration in the Northern Thailand were 45.3 ± 43.8, 79.2 ± 56.8 and 28.7 ± 21.0 µg/m3, respectively. The hotspot and PM10 levels showed high level in biomass burning season and the highest in March, the same trend pattern was observed every year. PM10 concentration during smoke episode was higher than those in non-smoke episode with statistic significant (p < 0.05). Cleared diurnal variations of PM10 level showed a bimodal pattern with peaks during 8.00–10.00 am as well as 7.00–9.00 pm in both episodes. The level of CO, SO2 and nitrogen oxides represented similar pattern variations. It is because these periods are rush hour duration with an increased traffic volume in every area of monitoring stations. The association between particulate matter and air pollutants showed strong positive relationship (p < 0.01). The results showed that both the vehicle emissions and biomass burning were major sources of atmospheric particle. Hazard index (HI) during long term exposure exceeded the acceptable level of non-carcinogenic adverse health risk (HI > 1).